A new genus and species of xanthoid crab (Decapoda: Brachyura) from offshore hard bank habitats in the Gulf of Mexico - Thoma, Brent P.; Felder, Darryl L. (Zootaxa, 2020)
Speciose populations of small xanthoid crabs on offshore banks and reefs of the northern Gulf of Mexico include a new species that is not assignable to presently named genera. Morphological diagnoses of the new genus and species are underpinned by previously published gene sequence analyses, originally misattributed to another species but now known to apply to this taxon. Herein named Guinope tiara n. gen., n. sp., the species shows molecular phylogenetic affinities with the family Linnaeoxanthidae Števčić, 2005, an ally of panopeid and pseudorhombilid crabs. Specimens from Occulina banks off the Florida Atlantic coast, previously regarded to represent Garthiope barbadensis (Rathbun, 1921), are not that species but instead morphologically assignable to Guinope n. gen. Whether they represent variants of Guinope tiara n. gen, n. sp. or a second species of the genus awaits the collection of fresh materials for DNA analyses.